STKIP Goes to Village, Solusi Mengatasi Learning Loss Selama Pandemi Covid-19 Bagi Anak-Anak Di Ledongara - Desak Made Anggraeni (Unram Journal of Community Service, 2023)
The impact of Covid-19 is being felt in all sectors of life, one of which is education. During the Covid-19 pandemic, the learning process changed from a face-to-face system to an online learning system. However, this learning system does not work effectively which has an impact on learning loss in children, especially for children in Ledongara. This impact was also felt by children in Ledongara - Southwest Sumba Regency - NTT. This condition is exacerbated by the location of the area which is above the hills and far from the crowds and access to electricity that has not been touched until the end of January 2022. The collaboration between STKIP Weetebula and UAJ Jakarta and BCA helped build a PLTS in Ledongara so that it can help residents in the area, especially children can facilitate learning activities in the evening. In the 2 years facing the Covid-19 pandemic, the learning process that has taken place in the Ledongara region has not been optimal. The transfer of knowledge that is expected to occur from the teacher to students cannot be carried out optimally so that it results in learning loss experienced by students. This learning loss condition is a condition that is not good because it will have an impact on decreasing the quality of education. The solution offered is the STKIP goes to village activity through tutoring activities, introduction to various science learning media, introduction to various simple practicum activities and Phet-assisted practicum related to science material. The training participants gave an extraordinary positive appreciation for the implementation of this activity because it can help improve students' understanding when they are still less effective during learning due to the pandemic and requested that this activity be carried out regularly